A Fourth Time of Trial: Towards an Implicit and Inclusive American Civil Religion - McDonald, Jermaine M. (Implicit religion, 2013)
This article revisits Robert Bellah's conception of civil religion in America (using his methodology of deconstructing presidential addresses and other important political discourses), to posit that America is in the midst of a fourth time of trial, for which consensus on American identity and meaning in the world is in jeopardy. To that end, I revisit Bellah's third time of trial to account for salient themes that have been added to American civil religion resulting from this period. Next, I analyze the public discourse of Presidents George W. Bush and Barack Obama regarding the impact of 9/11 on American attitudes towards Muslims in America, to determine how the tenets of American civil religion have been affirmed, challenged, and critiqued in this time of trial, arguing for the need of a more implicit and inclusive understanding of civil religion. Finally, I suggest examples of Muslim Americans contributing to the broadening of recognizably American identity that aligns with the ways in which the post-9/11 presidents have made the case for an increase in American tolerance and diversity.